A Comparative Study of Scopus and Web of Science: Climate Related Literature Retrieval - Das, Arijit; Mondal, Sukanya (Journal of Information and Knowledge, 2018)
There are various databases to retrieve information; sometimes users find it difficult to select the material to be read. To make the right decision for selecting the appropriate database there are some important factors such as coverage, functionality etc. This paper compares two popular bibliographic databases - Web of Science and Scopus for their coverage and retrieval of Climate related literature. Four keywords were used to carry out the searches and the paper examines the weakness and strength of these two databases.